Population genomics through time provides insights into the consequences of decline and rapid demographic recovery through head‐starting in a Galapagos giant tortoise. (13th August 2018) - Jensen, Evelyn L.; Edwards, Danielle L.; Garrick, Ryan C.; Miller, Joshua M.; Gibbs, James P.; Cayot, Linda J.; Tapia, Washington; Caccone, Adalgisa; Russello, Michael A.
Abstract: Population genetic theory related to the consequences of rapid population decline is well‐developed, but there are very few empirical studies where sampling was conducted before and after a known bottleneck event. Such knowledge is of particular importance for species restoration, given links between genetic diversity and the probability of long‐term persistence. To directly evaluate the relationship between current genetic diversity and past demographic events, we collected genome‐wide single nucleotide polymorphism data from prebottleneck historical (c.1906) and postbottleneck contemporary (c.2014) samples of Pinzón giant tortoises ( Chelonoidis duncanensis ; n  =   25 and 149 individuals, respectively) endemic to a single island in the Galapagos. Pinzón giant tortoises had a historically large population size that was reduced to just 150–200 individuals in the mid 20th century. Since then, Pinzón's tortoise population has recovered through an ex situ head‐start programme in which eggs or pre‐emergent individuals were collected from natural nests on the island, reared ex situ in captivity until they were 4–5 years old and subsequently repatriated. We found that the extent and distribution of genetic variation in the historical and contemporary samples were very similar, with the latter group not exhibiting the characteristic genetic patterns of recent population decline. No population structure was detected either spatially or temporally. We estimated an effective population size ( N e ) of 58 (95% CI = 50–69) for the postbottleneck population; no prebottleneck N e point estimate was attainable (95% CI = 39–infinity) likely due to the sample size being lower than the true N e . Overall, the historical sample provided a valuable benchmark for evaluating the head‐start captive breeding programme, revealing high retention of genetic variation and no skew in representation despite the documented bottleneck event. Moreover, this work demonstrates the effectiveness of head‐starting in rescuing the Pinzón giant tortoise from almost certain extinction.